Ecological Citizenship Discourse: A Critical Study of Citizenship Education in Indonesia - Kasmawati, Andi (Bina Nusantara University, 2023)
The research discussed that global and ecological citizenship discourse became vital for all current citizenship models; apart from the relational needs between humans and the environment, nature also needed to be preserved for survival and efforts to increase civic values. However, this conceptual-theoretical debate about the development and influence of this discourse created an antinomy among the dominant theories that had a place in contemporary citizenship discourse. Qualitatively, the research contributed to exploring the development of global and ecological citizenship discourse and its influence on students’ experiences of citizenship in Indonesia. It was built on ‘theoretical eclecticism’ and focused on the respondent’s ‘cognitive response’ combined with a critical realism perspective to analyze data, which was obtained randomly in various places and students from various majors by prioritizing the main aspects: mental existence; external existence; and essence as a knowledge domain; awareness; and their experiences. Each meeting lasted between 30 to 45 minutes with 100 respondents. Descriptively, the research results indicate that the development of global and ecological citizenship discourse has not received attention and has a significant impact on the discourse of education and citizenship experience in Indonesia. The ecological dimension lacks or does not yet have a close relationship with all other dimensions in the citizen’s experience as a form of civic virtue, including knowledge, awareness, and actions, both economic, social, and political.